Group B streptococcus drug resistance in pregnant women in Iran: a meta-analysis - Farzad Khademi; Amirhossein Sahebkar (Elsevier, 2020)
Streptococcus (S.) agalactiae colonizes in the female genitourinary and lower gastrointestinal tracts and is responsible for a wide range of infections in newborns, pregnant women and non-pregnant adults. Therefore, antibiotic prophylaxis and infection treatment against S. agalactiae is important. The aim of this study was to determine the prevalence of S. agalactiae antibiotic resistance in Iranian patients, especially among pregnant women. A systematic literature search was conducted in PubMed, Scopus, Google Scholar and the Scientific Information Database (SID) databases by using related keywords and without any time limitation. A total of 26 studies reporting the prevalence of S. agalactiae antibiotic resistance in Iran met our predefined inclusion and exclusion criteria and were included in the meta-analysis. High rates of S. agalactiae antibiotic resistance in pregnant women were found against tetracycline (96.2%), trimethoprim-sulfamethoxazole (84.7%), cefotaxime (41.3%), clindamycin (26.8%) and erythromycin (21%). Additionally, resistance to penicillin (4.2%), ampicillin (2.7%), cefazolin (7.6%), vancomycin (2.4%), ceftriaxone (12.5%), ciprofloxacin (13.6%) and nitrofurantoin (0%) was low. Our results revealed that penicillin and ampicillin among penicillin-tolerant Iranian pregnant women, and vancomycin and cefazolin among penicillin-allergic women are still drugs of choice in intrapartum prophylaxis for preventing S. agalactiae vertical transmission and early-onset neonatal disease.